The effects of growing media on morphological attributes of containerized oriental spruce seedlings - Ayan, Sezgin; Tilki, Fahrettin (Acta Agronomica Hungarica ", 55, 363-373, (2007), 2007)
This study was designed to investigate the influence of growing media consisted of different components on morphological attributes of oriental spruce seedlings. Eighteen different components of Barma peat (BP), tea residue compost (CTR), fine pumice (FP), coarse pumice (CP), perlite (P) and zeolite (Z) were prepared as a growing medium component. Growing medium component did not significantly affect shoot height (SH), root collar diameter (RCD), shoot root ratios and dry root percentage (DRP) of 2-year-old seedlings. However, root dry weight (RDW) and shoot dry weight (SDW) showed significant differences among different growth media. The maximum SDW (3.244 g) were determined for the mixtures of BP (0.5) + CTR (0.2) + CP (0.2) + Z (0.1) medium while the mixtures of BP (0.6) + P (0.2) + Z (0.2) medium produced minimum SDW (1.593 g). In addition, the maximum RDW (1.824 g) was determined for BP (0.5) + CTR (0.2) + CP (0.2) + Z (0.1) medium while BP (0.6) + CP (0.2) + Z (0.2) medium resulted in the lowest RDW (1.013 g). Zeolite added to mixtures of growing media increased the SDW and RDW of oriental spruce seedlings, and therefore, natural zeolite could be used as a substrate such as pumice and perlite in nurseries in Turkey. Since Turkey has 45.8 billions of zeolite potential, using zeolite in nurseries may reduce the costs significantly.
Keywords: Growing media, Picea orientalis, seedling attributes, zeolite